Did the Cold War Produce Development Clusters in Africa? - Paul Castaneda Dower; Gunes Gokmen; Michel Le Breton; Shlomo Weber (Lund University, School of Economics and Management, Department of Economics, 2021)
This paper examines the lasting impact of the alignment of African countries during the Cold War on their modern economic development. We find that the division of the continent into two blocs (East/West) led to two clusters of development outcomes that reflect the Cold War's ideological divide. To determine alignment, we introduce a non-cooperative game of social interactions where each country chooses one of the two existing blocs based on its predetermined bilateral similarities with other members of the bloc. We show the existence of a strong Nash equilibrium in our game and apply the celebrated MaxCut method to identify such a partition. The alignment predicts UN General Assembly voting patterns during the Cold War but not after. Our approach, linking global political interdependence to distinct development paths in Africa, relies on history to extract a micro-founded treatment assignment, while allowing for an endogenous, process-oriented view of historical events.
Keywords: C62; C72; F54; F55; N47; N47; O19; O57; Y10; 330; Cold War; Political Alliances; Africa; Blocs; Development Clusters; Strong Nash Equilibrium; Landscape Theory